1997
DOI: 10.1165/ajrcmb.17.6.2820
|View full text |Cite
|
Sign up to set email alerts
|

Role of IFN- γ in the Inhibition of the Allergic Airway Inflammation Caused by IL-12

Abstract: T-helper 2 (Th2)-like cells are thought to play a crucial role in the pathogenesis of the eosinophilic airway inflammation observed in asthma. In a murine model of allergen-induced airway eosinophilia and bronchial hyperresponsiveness (BHR), we have shown that interleukin (IL)-12 can suppress antigen-induced airway changes despite the presence of circulating specific IgE. In the present study, we investigated the role of interferon-gamma (IFN-gamma) in the inhibitory effects of IL-12 on allergic airway inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
41
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 21 publications
2
41
1
Order By: Relevance
“…Notably, we also found that IFN-␥ can suppress the development of airway neutrophilia in OVA-challenged OTII mice, as has been reported in models of Th2-associated airway eosinophilia. 34 Thus, our evidence also indicates that Th1 cells can negatively regulate aspects of Th17 cell and IL-17-dependent inflammation, at least in this model system. The results obtained in our analyses of the leukocytes present after OVA challenge in the BALF specimens derived from the many different types of cytokine-, receptor-or mast cell-deficient OVA-specific TCR-expressing OTII mice investigated in this model are summarized in Table S1.…”
supporting
confidence: 58%
“…Notably, we also found that IFN-␥ can suppress the development of airway neutrophilia in OVA-challenged OTII mice, as has been reported in models of Th2-associated airway eosinophilia. 34 Thus, our evidence also indicates that Th1 cells can negatively regulate aspects of Th17 cell and IL-17-dependent inflammation, at least in this model system. The results obtained in our analyses of the leukocytes present after OVA challenge in the BALF specimens derived from the many different types of cytokine-, receptor-or mast cell-deficient OVA-specific TCR-expressing OTII mice investigated in this model are summarized in Table S1.…”
supporting
confidence: 58%
“…In contrast to IL-12's effects on AHR, the inhibitory effects of IL-12 on BAL eosinophilia have been shown to be only partially IFN-y mediated (47). Such partial IFN-y dependence in these studies could have resulted from an incomplete neutralization of the cytokine in vivo with anti-IFN-y mAb.…”
mentioning
confidence: 67%
“…Such partial IFN-y dependence in these studies could have resulted from an incomplete neutralization of the cytokine in vivo with anti-IFN-y mAb. However, a recent study by Brusselle et al using IFN-y receptor-deficient mice has virtually excluded this possibility (47). Interestingly, they demonstrated that while antigen-induced airway eosinophilia is largely IFN-y-independent when IL-12 is given during secondary allergen exposure, when it is given before sensitization, BAL eosinophilia is IFN-y dependent (47).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reciprocal regulation between Th1 and Th2 cytokines has been documented previously. [16][17][18][19] Based on the unique cytokine pattern associated with ED, we propose that TNF-a elevation might inhibit the IL-4 production and impair the Th1/Th2 balance, consequently contributing to the pathogenesis of ED. The aetiology of ED has been suggested to be multifactorial.…”
mentioning
confidence: 99%